U1 small nuclear ribonucleoprotein particle-protein interactions are revealed in Saccharomyces cerevisiae by in vivo competition assays. - Stutz, F (1993)
Two highly conserved regions of the 586-nucleotide yeast (Saccharomyces cerevisiae) U1 small nuclear RNA (snRNA) can be mutated or deleted with little or no effect on growth rate: the universally conserved loop II (corresponding to the metazoan A loop) and the yeast core region (X. Liao, L. Kretzner, B. Séraphin, and M. Rosbash, Genes Dev. 4:1766-1774, 1990). To examine the contribution of these regions to U1 small nuclear ribonucleoprotein particle (snRNP) activity, a competitor U1 gene, encoding a nonfunctional U1 snRNA molecule, was introduced into a number of strains carrying a U1 snRNA gene with loop II or yeast core mutations. The presence of the nonfunctional U1 gene lowered the growth rate of these mutant strains but not wild-type strains, consistent with the notion that mutant U1 RNAs are less active than wild-type U1 snRNAs. A detailed analysis of the U1 snRNA levels and half-lives in a number of merodiploid strains suggests that these mutant U1 snRNAs interact with U1 snRNP proteins less well than do their wild-type counterparts. Competition for protein factors during snRNP assembly could account for a number of previous observations in both yeast and mammalian cells.